2018
DOI: 10.12659/msm.909011
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Enhances the Hypoglycemic Effect of Insulin in L6 Cells via Phosphatidylinositol-3-Kinase (PI3K)/Protein Kinase B (AKT)/Glucose Transporter 4 (GLUT4) Signaling Pathway

Abstract: BackgroundDiabetes mellitus (DM) is characterized by a decreased blood level of glutamine (Gln), which may contribute to the disturbance in the effect of insulin on skeletal muscle. Therefore, it is crucial to study how to improve the effect of insulin on skeletal muscle by increasing Gln. In the present study, we investigated the effect of Gln on the hypoglycemic action of insulin in skeletal muscle L6 cells at high glucose levels through the insulin signaling pathway and glycogen synthesis pathway.Material/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…After stimulation with 100 nM of Insulin (Sigma Aldrich, St. Louis, MO), they were fixed with 4% paraformaldehyde without permeabilization and subjected to HA staining using a rabbit monoclonal anti-HA antibody (Rockland, Limerick, PA) followed by Alexa Fluor 594-conjugated goat anti-rabbit IgG (Abcam, Cambridge, UK). The Alexa Fluor 595/GFP ratio was determined by quantitative fluorescence microscopy as described previously 27 . To avoid cell selection bias fields, cells expressing the HA–Glut4-eGFP were randomly chosen in the GFP channel blinded to the expression of HA–Glut4-GFP on the plasma membrane (Alexa Fluor 594 channel).…”
Section: Methodsmentioning
confidence: 99%
“…After stimulation with 100 nM of Insulin (Sigma Aldrich, St. Louis, MO), they were fixed with 4% paraformaldehyde without permeabilization and subjected to HA staining using a rabbit monoclonal anti-HA antibody (Rockland, Limerick, PA) followed by Alexa Fluor 594-conjugated goat anti-rabbit IgG (Abcam, Cambridge, UK). The Alexa Fluor 595/GFP ratio was determined by quantitative fluorescence microscopy as described previously 27 . To avoid cell selection bias fields, cells expressing the HA–Glut4-eGFP were randomly chosen in the GFP channel blinded to the expression of HA–Glut4-GFP on the plasma membrane (Alexa Fluor 594 channel).…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we will point out only a few members of this enormous group. For instance, glutamine (Gln) supplementation Gln increases the expression of key PI3K signaling molecules (PI3K, PDK1, and GLUT4) and promotes AKT phosphorylation, GLUT4 translocation, and glucose uptake in the presence of insulin during exposure to hyperglycemia [64]. An epidemic of obesity and numerous side effects of drugs that increase insulin sensitivity has caused the great interest among scientists to search for natural sensitizers.…”
Section: Insulin-sensitizing Factorsmentioning
confidence: 99%
“…PI3K/Akt/mTOR is a signal pathway closely related to insulin signal transduction (6,24) . The expression of PI3K and phosphorylation of Akt in kidney, liver, skeletal muscle and adipose tissue of DM rats were signi cantly decreased; in the development of DM, persistent hyperglycemia can promote the activation of PI3K / Akt signaling pathway, and ultimately accelerate the development of DM (37) . This study found that overexpression of Rab35 inhibited PI3K/Akt/mTOR signaling pathway and promoted insulin secretion; when Rab35 was inhibited, PI3K/ Akt/mTOR pathway was activated and insulin secretion was down regulated.…”
Section: Discussionmentioning
confidence: 94%